Fructose intake and food sources in West Australian adolescents. Issue 2 (14th March 2013) - Woolley, Susan E.; Sherriff, Jill; Oddy, Wendy H.; O' Sullivan, Therese A.
Abstract: Aim: This research aimed to cross‐sectionally quantify fructose consumption and identify major food sources of fructose in adolescents participating in the 14‐year follow up of the Western Australian Pregnancy Cohort (Raine) Study. Methods: Subjects were 822 adolescents aged 13–15 years participating in the Raine Study. Dietary intake was assessed by 3‐day food records and entered in the FoodWorks dietary analysis program. Total fructose values for individual foods were linked from the Nutrient Tables for use in Australia, the University of Minnesota Nutrition Coordinating Centre Food and Nutrient Database, and the Canadian Nutrient File. Results: Fructose contributed 9.1% of total energy intake for the group. Boys reported higher absolute fructose intakes than girls (58.9 g ± 26.6 g vs 48.3 g ± 20.1 g, respectively, P < 0.001), while girls had higher energy adjusted fructose intakes than boys (55.7 g ± 16.1 g vs 51.8 g ± 20.2 g, respectively, P = 0.002). Major food sources of total fructose were beverages, in particular soft drinks, followed by fruit and confectionery. No significant associations were found between fructose intake and level of physical activity, Body Mass Index or socioeconomic status indicators in unadjusted analyses; however, adolescents from higher socioeconomic groups consumed more fructose from fruit, whereas adolescents from lower socioeconomic groups consumed more fructose from beverages. Conclusions: To our knowledge, this is the first study to describe fructose intake and food sources in Australian adolescents. Results are similar to those previously reported in studies of US adolescents.